GASTROINTESTINAL PARASITES IN FREE-RANGING TAYASSU PECARI AND PECARI TAJACU FROM THE PILON LAJAS BIOSPHERE RESERVE AND INDIGENOUS TERRITORY, BENI – BOLIVIA - Limachi Quiñajo, Rolando (2014)
Adult and immature gastrointestinal parasites from 47 tayassuids (27 Tayassu pecari and 20 Pecari tajacu) hunted for human consumption at the Pilon Lajas Biosphere Reserve and Indigenous Territory, Bolivia, were identified. Parasite eggs and oocysts were identified by fecal flotation and sedimentation, while adult parasites were obtained from the digestive tract and collected through the Travassos method for morphometric identification. Four nematode species (Texicospirura turki, Monodontus aguiari, Eucyathostomum dentatum and Ascaris sp.), one cestode (Monienzia benedeni), one trematode (Stichorchis giganteus) and Eimeria spp. oocysts were detected. Parasites of the Ascaris genera were detected only in T. pecari while the rest of the parasites were found in both tayassuid species. This study provides the first report for these parasites in peccaries from Bolivia. Given the close contact between Amazon inhabitants and tayassuids, and considering the zoonotic nature of Ascaris infections, further investigations into potential peccary to human transmission are warranted.